Adaptive sliding mode observation in a network of dynamical systems. (25th January 2016) - Menon, Prathyush P.; Edwards, Christopher; Shtessel, Yuri B.
Summary: This paper considers the problem of reconstructing state information in all the nodes of a complex network of dynamical systems. The individual nodes comprise a known linear part and unknown but bounded uncertainties in certain channels of the system. A supervisory adaptive sliding mode observer configuration is proposed for estimating the states. A linear matrix inequality (LMI) approach is suggested to synthesise the gains of the sliding mode observer. Although deployed centrally to estimate all the states of the complex network, the design process depends only on the dynamics of an individual node of the network. The methodology is demonstrated by considering a network of Chua oscillators. Copyright © 2016 John Wiley & Sons, Ltd.